A Comparative Study Of Job Satisfaction Of Employees In German And Japanese Organization - Abdullah, Mohamed Yusuf Khatri (1996)
This study was conducted to examine the difference in job satisfaction of production workers employed in Japanese and German organizations. In addition it was designed to sec the effect of demographic variables (age, sex, experience, income and marital status) on job satisfaction of -employees in these two organizations. Using the questionnaire technique, data was collected from 56 and 60 production worker’s working in Japanese and German organizations respectively. The results show that neither the ownership nor the demographic variables influenced the job satisfaction scores.